The effects of cues on neurons in the basal ganglia in Parkinson's disease - Sarma, Sridevi V.; Cheng, Ming L.; Eden, Uri T.; Williams, Ziv; Brown, Emery N.; Eskandar, Emad (Frontiers in Integrative Neuroscience, 2012)
Visual cues open a unique window to the understanding of Parkinson’s disease (PD). These cues can temporarily but dramatically improve PD motor symptoms. Although details are unclear, cues are believed to suppress pathological basal ganglia (BG) activity through activation of corticostriatal pathways. In this study, we investigated human BG neurophysiology under different cued conditions. We evaluated bursting, 10-30Hz oscillations (OSCs), and directional tuning (DT) dynamics in the subthalamic nucleus activity while 7 patients executed a two-step motor task. In the first step (predicted +cue), the patient moved to a target when prompted by a visual go cue that appeared 100% of the time. Here, the timing of the cue is predictable and the cue serves an external trigger to execute a motor plan. In the second step, the cue appeared randomly 50% of the time, and the patient had to move to the same target as in the first step. When it appeared (unpredicted +cue), the motor plan was to be triggered by the cue, but its timing was not predictable. When the cue failed to appear (unpredicted -cue), the motor plan was triggered by the absence of the visual cue. We found that during predicted +cue and unpredicted -cue trials, OSCs significantly decreased and DT significantly increased above baseline, though these modulations occurred an average of 640 milliseconds later in unpredicted -cue trials. Movement and reaction times were comparable in these trials. During unpredicted +cue trials, OSCs and DT failed to modulate though bursting significantly decreased after movement. Correspondingly, movement performance deteriorated. These findings suggest that during motor planning either a predictably timed external cue or an internally generated cue (generated by the absence of a cue) trigger the execution of a motor plan in premotor cortex, whose increased activation then suppresses pathological activity in STN through direct pathways, leading to motor facilitation in PD.